Digging Deeper for Agricultural Resources, the Value of Deep Rooting. (April 2020) - Thorup-Kristensen, Kristian; Halberg, Niels; Nicolaisen, Mette; Olesen, Jørgen Eivind; Crews, Timothy E.; Hinsinger, Philippe; Kirkegaard, John; Pierret, Alain; Dresbøll, Dorte Bodin
Abstract : In the quest for sustainable intensification of crop production, we discuss the option of extending the root depth of crops to increase the volume of soil exploited by their root systems. We discuss the evidence that deeper rooting can be obtained by appropriate choice of crop species, by plant breeding, or crop management and its potential contributions to production and sustainable development goals. Many studies highlight the potentials of deeper rooting, but we evaluate its contributions to sustainable intensification of crop production, the causes of the limited research into deep rooting of crops, and the research priorities to fill the knowledge gaps. Highlights: Recent studies have documented highly significant differences among current and potential crops, as well as genotypic differences, in the ability for deep rooting. Results have shown significant effects of deep roots on deep soil water and nutrient uptake. Technological improvements of nondestructive methods, such as rhizotron and image analysis based root observations, soil water sensors, and isotope tracers for uptake studies, allow combined and dynamic studies of root development and function. The quest for sustainable intensification of crop production promotes the interest in understanding and exploiting the potential contribution by deeper soil layers. Deep layers may contribute to resource supply for crop growth, reducing losses to the environment and deep C sequestration to mitigate climate change.